Efektivitas Ice Breaking Pada Model Pembelajaran Make A Math Terhadap Hasil Belajar Matematika Siswa SMP Negeri 4 Satu Atap Sampolawa - Santi, Wa; Lestari, Dian; Usa, Suwarni La (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2025)
The Formulation in this research are: 1) whether the application of Ice Breaking in mathematics learning using the Make A Match learning model is effective on the mathematics learning outcomes if students at SMP Negeri 4 Satu Atap Sampolawa; 2) Is the application of the Make A Match learning model without the application of Ice Breaking effective in mathematics learning on the mathematics learning outcomes of students at SMP Negeri 4 Satu Atap Sampolawa; 3) Which is more effective between the application of Ice Breaking in the Make A Match learning model without the application of Ice Breaking in mathematics learning for students at SMP Negeri 4 Satu Atap Sampolawa. The aim of this research is to determine 1) the effectiveness of implementing Ice Breaking in mathematics learning outcomes of students at SMP Negeri 4 Satu Atap Sampolawa. 2) the effectiveness of implementing the Make A Match model without implementing Ice Breaking in mathematics learning on the mathematics learning outcomes of students at SMP Negeri 4 Satu Atap Sampolawa. 3) the effectiveness of the application of Ice Breaking in the Make A Match learning model and the application of the Make A Match learning model without the application of Ice Breaking in mathematics learning on the mathematics learning outcomes of students at SMP Negeri 4 Satu Atap Sampolawa. This research uses a quantitative approach with a quasi-experimental type. The population of this study were all students in class VIII of SMP Negeri 4 Satu Atap Sampolawa which consisted of 2 classes with a total of 34 students. The sample in this study was class VIII. 1 as experimental class 1 and class VIII 2 as an experimental 2. Data collection in this research used tests in the form of essays. Hypothesis testing techniques use paired sample tests and independent sample tests. The research results show that the application of Ice Breaking in the Make Match learning model and the application of the Make A Match learning model without Ice Breaking in mathematics learning on the subject of straight line equations are both equally effective. Descriptively, the average scores for experimental class 1 and experimental class 2 were respectively 64.50 and 67.73. Based on the results of the results of the comparative analysis between experimental class 1 and experimental class 2, it was concluded that the application of Ice Breaking in the Make A Match learning model was not more effective than implementing the Make A Match learning model without Ice Breaking. This is proven based on the results of students’ data analysis which shows that the value is 0.916 with a significance value of p-value greater than the significance level (0.373>0.05).